183k views
1 vote
S=L (1 - r), for r

This is all it says, you are solving for r, the instructions just say solve for r

User BassT
by
5.3k points

1 Answer

6 votes

Solving for r is the same as isolating it. Since we have (1-r) being multiplied by L, we want to divide it out so we can work with (1-r), so:


(S)/(L)=1-r

Now, we want to make -r positive, so we multiply both sides by negative 1:


-(S)/(L)=r-1

Now, to isolate r we want to add 1 to both sides, so:


1-(S)/(L)=r

and we're done.

User Naseefo
by
4.5k points